STRATEGI POLITIK PRABOWO SUBIANTO-SANDIAGA SALAHUDDIN UNO DALAM MENINGKATKAN JUMLAH SUARA DI CAKUNG JAKARTA TIMUR PADA PILPRES TAHUN 2019 - Andani Syakira Putri (2024)
This research explores the political strategy of Prabowo Subianto-Sandiaga Uno in achieving victory in Cakung District, East Jakarta, in the 2019 Presidential General Election. With an explanatory qualitative approach, data was obtained through interviews with DPC Gerindra East Jakarta and the Prabowo-Sandiaga success team, as well as document studies . Even though pair number 01 won nationally, Prabowo-Sandiaga managed to excel in East Jakarta. The analysis shows the evolution of political strategy from defensive in the 2014 presidential election to offensive in 2019, reflecting adaptation to changing political dynamics. A winning strategy involves hard work, broad support, and a combination of offensive (targeting the opponent's vote base) and defensive (maintaining the support base). Policies responsive to local characteristics, positive images through the media, and emotional connections with voters also played key roles in the pair's success